Effectiveness of WHO dengue management protocol: An observational study - Nishanth Rajan; Priya Jose; Peter Prasanth Kumar Kommu; Manikandan Mani; Lalitha Krishnan (Wolters Kluwer Medknow Publications, 2021)
Background: Dengue fever (DF) has become a worldwide health problem. There are only a few studies assessing management based on the classification by the World Health Organization (WHO). Hence, we aimed at assessing the outcome of children with DF before and after the implementation of the WHO protocol. Subjects and Methods: A retrospective hospital-based comparative study was done in a tertiary care center, Puducherry, to study the outcome of children diagnosed with DF before and after the implementation of WHO management 2012 protocol in the year 2014. All children (0-14 years) who were diagnosed with DF (NS1Ag or IgM ELISA positivity) during 2012-2016 were included. Medical records with incomplete data were excluded. They were divided into two groups: Group I - Children admitted for treatment of DF between January 2012 and December 2013 (24 months) and managed by close clinical monitoring and Group II - Children admitted for treatment of DF between January 2014 and December 2016 (36 months) and managed as per WHO protocol. Results: There was no statistically significant difference in the signs of shock and mortality between the groups. There was statistically significant difference of children with fluid overload during the recovery phase in Group II when compared with Group I. Conclusions: Close clinical monitoring during the critical phase may reduce the signs of fluid overload during the recovery phase.